2014
DOI: 10.1177/1359104514538434
|View full text |Cite
|
Sign up to set email alerts
|

Affect Consciousness in children with internalizing problems: Assessment of affect integration

Abstract: Affect integration was operationalized through the Affect Consciousness (AC) construct as degrees of awareness, tolerance, nonverbal expression and conceptual expression of 11 affects. These aspects are assessed through a semi-structured Affect Consciousness Interview (ACI) and separate rating scales (Affect Consciousness Scales (ACSs)) developed for use in research and clinical work with adults with psychopathological disorders. Age-adjusted changes were made in the interview and rating system. This study exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 29 publications
6
31
0
Order By: Relevance
“…This interpretation fits well with the theoretical propositions by Izard [50], Krystal [51] [19], and Taarvig et al [20]. We believe that support for this conjecture has not previously been so clearly demonstrated in the specific context of PD pathology as in the present study.…”
Section: Ai and Personality Functioningsupporting
confidence: 93%
See 2 more Smart Citations
“…This interpretation fits well with the theoretical propositions by Izard [50], Krystal [51] [19], and Taarvig et al [20]. We believe that support for this conjecture has not previously been so clearly demonstrated in the specific context of PD pathology as in the present study.…”
Section: Ai and Personality Functioningsupporting
confidence: 93%
“…This interpretation fits well with the theoretical propositions by Izard [ 50 ], Krystal [ 51 ], Monsen & Monsen [ 13 ], Solbakken, Hansen, & Monsen [ 15 ], Stolorow, Atwood, & Brandchaft [ 7 ], and Tomkins [ 16 , 17 ] and empirical findings by, e.g., Monsen et al [ 6 ], Solbakken, Hansen, Havik, & Monsen [ 22 ], Solbakken, Hansen, Havik, & Monsen [ 21 ], Solbakken et al [ 19 ], and Taarvig et al [ 20 ]. We believe that support for this conjecture has not previously been so clearly demonstrated in the specific context of PD pathology as in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Affect Consciousness Interview Affect integration was assessed using the Affect Consciousness Interview (ACI), a semi-structured clinical interview ( 25) available for children (3). Affect integration in the ACI is operationalized as the "degrees of awareness, tolerance, emotional /nonverbal and conceptual expressivity" across a set of affective states.…”
Section: Assessment Of Affect Integrationmentioning
confidence: 99%
“…Consciousness construct and assessed by use of the semi-structured Affect Consciousness Interview (Monsen, Monsen, Hansen, & Solbakken, 2008). Numerous studies have indicated the usefulness of this conceptualization at both clinical and theoretical levels (e.g., Monsen, Ødegård, & Melgård, 1989;Monsen et al, 1996;Monsen & Monsen, 1999;McCullough Vaillant, 1997;Falkenström, Solbakken, Möller, Lech, Sandell, & Holmqvist, 2014;Gude, Monsen, & Hoffart, 2001;Normann-Eide, Johansen, Normann-Eide, Egeland, & Wilberg, 2013;Waller & Scheidt, 2004;Holmqvist, 2008;Lech, Andersson, & Holmqvist, 2008;Choi-Kain & Gunderson, 2008;Solbakken et al, 2011b;Solbakken et al, 2012;Taarvig, Solbakken, Grova, & Monsen, 2014).…”
Section: Affect Integration Has Been Commonly Operationalized Throughmentioning
confidence: 99%